Species and Metabolic Pathways Involved in Bioremediation of Vietnamese Soil From Bien Hoa Airbase Contaminated With Herbicides - Nguyen, Thi Lan Anh; Dang, Ha Thi Cam; Koekkoek, Jacco; Braster, Martin; Parsons, John R.; Brouwer, Abraham; de Boer, Tjalf; van Spanning, Rob J. M. (Frontiers in Sustainable Cities, 2021)
Four bacterial strains were isolated from enrichment cultures inoculated with soil from Bien Hoa military base in Vietnam contaminated with the herbicides 2,4-dichlorophenoxyacetate (2,4-D) and 2,4,5-trichlorophenoxyacetate (2,4,5-T). They were classified as Pseudomonas aeruginosa BT1 2.2, Sphingomonas histidinilytica BT1 5.2, Bordetella petrii BT1 9.2, and Achromobacter xylosoxidans BT1 10.2. All 4 were able to degrade 2,4-D and 2,4,5-T, but only the last 3 species used them as the sole sources of carbon and energy. Mass balance analyses suggest that between 33 to 46% of the carbon in the herbicides is incorporated into dry weight. We obtained insight into their degradation pathways by the genomic analysis of these strains. A tfdCDEF gene cluster was found in A. xylosoxidans BT1 10.2 with amino acid sequences of their gene products showing high identity to those in B. petrii DSM12804. B. petrii BT1 9.2 has a full complement of the tfdABCDEF genes. Surprisingly, the gene organization along with the amino acid sequences of the gene products are virtually identical to those of Cupriavidus pinatubonensis JMP134, referred to as type I tfd genes, and different from those of A. xylosoxidans BT1 10.2 and B. petrii DSM12804. We hypothesize that some of the genetic potential to degrade the herbicides has been recruited in recent mating events between these species and other members of the proteobacteria. This is the first report showing that Bordetella petrii BT1 9.2 emerges as a key player in the degradation of 2,4-D.